2021
DOI: 10.3390/jpm11111048
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea Induces Bone Marrow Mesenchymal Stromal Cells Senescence and Modifies Cell Functionality In Vitro

Abstract: Hydroxyurea (HU) is an antineoplastic agent that functions as an antimetabolite compound by inhibiting the ribonucleotide reductase. HU acts mainly as a cytostatic drug that through DNA replication stress may trigger a premature senescence-like cell phenotype, though its influence on bone marrow-derived mesenchymal stem/stromal cell (BMMSC) functions has not elucidated yet. Our results indicate that HU inhibits the growth of human BMMSC alongside senescence-like changes in both morphology and replicative poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…It is well known that β-gal is overexpressed in senescent cells; therefore, the senescent cells were selected as a research model for β-gal activity. HU is a water-soluble antiproliferative agent, which can inhibit the antimetabolic substances of ribonucleotide reductase. , Ribonucleotide reductase leads to the depletion of deoxyribonucleotides and significantly reduces cell proliferation, thus inducing cell senescence of healthy cells and cancer cells in vitro . Therefore, three different cell lines were used, PC-12 (Figure S15a), Hep G2 (Figure a), and RAW 264.7 cells (Figure S16a), for living cell senescence experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that β-gal is overexpressed in senescent cells; therefore, the senescent cells were selected as a research model for β-gal activity. HU is a water-soluble antiproliferative agent, which can inhibit the antimetabolic substances of ribonucleotide reductase. , Ribonucleotide reductase leads to the depletion of deoxyribonucleotides and significantly reduces cell proliferation, thus inducing cell senescence of healthy cells and cancer cells in vitro . Therefore, three different cell lines were used, PC-12 (Figure S15a), Hep G2 (Figure a), and RAW 264.7 cells (Figure S16a), for living cell senescence experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that long-term injection and absorption of d -galactose can cause symptoms similar to natural aging. d -Galactose induces senescence by reducing respiratory chain enzyme activity and ATP synthesis, leading to mitochondrial dysfunction and increasing ROS production . HU is also considered to be a drug that causes senescence and exerts an antimetabolic compound effect by inhibiting ribonucleotide reductase . Therefore, D-galactose- and HU-induced living mice senescence were used as the model for in vivo imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, chemotherapy is known as an inducer of changes in both hematopoietic compartments and MSC functions. The authors investigated how hydroxyurea, an inhibitor of ribonucleotide reductase, alter human MSC differentiation and immunosuppressive functions [ 7 ]. This study showed that hydroxyurea induced MSC senescence including cell proliferation arrest, which suggests a potential “therapy-induced senescence” effect.…”
mentioning
confidence: 99%